The State of the Art in the Biophilic Construction of Healthy Spaces for People - Natividad Buceta-Albillos; Esperanza Ayuga-Téllez (Buildings, 2024)
Human beings need a connection to nature for their overall well-being, as highlighted by numerous publications. Housing is an extension of people’s lives. Confinement due to the COVID-19 pandemic, the rise of sustainability, longevity and the digital society are placing value on more sustainable and healthy construction for people’s well-being and quality of life. These premises motivate this study of the state of the art of biophilic design with a therapeutic and social approach. The main objective of this research is to investigate the evolution of the concept of biophilia in healthy buildings for people and the environment, analysing the current situation and identifying the main theories, models and applications. This research employs the six-step methodology for state-of-the-art analysis (SotA), using the process of reflexivity throughout this study. There are very few scientific studies that measure the positive impact of biophilic design on people’s well-being, and they tend to take the form of scientific discussion rather than evidence; this is their main limitation. Our recommendation is to identify new quantitative research on the biophilic impact on humans of healthy spaces in order to evaluate their effects.